(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
The origins of the idea of Russkij mir ABSTRACT: The doctrine of Russkij mir is the result of a long historical process marked by the progressive distancing of Russian Orthodoxy from Constantinople with the refusal of the Grand Prince of Moscow to accept the decisions of the Council of Florence. In the space of a few years, the metropolis of Moscow proclaimed its de facto autocephaly and the bond of subordination of the Sacerdotium to the Imperium was strengthened, especially starting from the Council of 1503 which saw the monastic current led by Iosif of Volokolamsk, who stated a close bond between Church and sovereign. prevail on that represented by Nil Sorsky, who supported the independence of the Church from civil power. At the beginning of the 16th century, the monk Filofej from the Pskov region enunciated the theory of the Moscow third Rome and the transfer of the imperial capital from Constantinople to Moscow. Since then the symphonic relationship between Church and Empire has been upset, no longer signifying the harmonious collaboration between them, but the prevalence of civil power over religious power, which will culminate in 1721 with Peter the Great’s decision to abolish the Patriarchate established in 1589. From then on the history of the Church will be that of the State. With the end of Bolshevism which marked the full subjugation of the Church, a new symphony was reconstituted between civil and religious power: the latter provides the former with the theological justification for the affirmation of Russkij mir, or the obsessive claim to also impose manu military the hegemony of Moscow and the supremacy of its Orthodoxy as the only way to eliminate Evil and impose Good in the reconstituted great Empire of Russia.